2021
DOI: 10.3390/cells10123336
|View full text |Cite
|
Sign up to set email alerts
|

Blood Immunoproteasome Activity Is Regulated by Sex, Age and in Chronic Inflammatory Diseases: A First Population-Based Study

Abstract: Dysfunction of the immunoproteasome has been implicated in cardiovascular and pulmonary diseases. Its potential as a biomarker for predicting disease stages, however, has not been investigated so far and population-based analyses on the impact of sex and age are missing. We here analyzed the activity of all six catalytic sites of the proteasome in isolated peripheral blood mononuclear cells obtained from 873 study participants of the KORA FF4 study using activity-based probes. The activity of the immuno- and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…It also changes with age, as almost all catalytic activities of the proteasome were activated in aged women while maintained in ageing men. Moreover, we showed distinct sex-related activation patterns of standard and immunoproteasome active sites in chronic inflammatory diseases such as diabetes, asthma, cardiovascular or chronic obstructive pulmonary diseases [38]. In accordance with these data, a recent study has also suggested profiling the activity of PBMC's immunoproteasome as a sensitive biomarker for the disease activity of Systemic juvenile idiopathic arthritis (sJIA), enabling the detailed evaluation of response to treatment.…”
Section: Standard-and Immunoproteasome Activity Profiles In Health An...supporting
confidence: 78%
See 4 more Smart Citations
“…It also changes with age, as almost all catalytic activities of the proteasome were activated in aged women while maintained in ageing men. Moreover, we showed distinct sex-related activation patterns of standard and immunoproteasome active sites in chronic inflammatory diseases such as diabetes, asthma, cardiovascular or chronic obstructive pulmonary diseases [38]. In accordance with these data, a recent study has also suggested profiling the activity of PBMC's immunoproteasome as a sensitive biomarker for the disease activity of Systemic juvenile idiopathic arthritis (sJIA), enabling the detailed evaluation of response to treatment.…”
Section: Standard-and Immunoproteasome Activity Profiles In Health An...supporting
confidence: 78%
“…This led us to suggest that proteasome activity profiling in PBMCs might serve as a biomarker for inflammation and pathology severity. We corroborated this concept by examining the proteasome activity profile of PBMCs in the large population-based KORA F4 cohort of 924 subjects [38]. In this study, we demonstrated for the first time, that the proteasome activity profile in PBMCs has a strong sex dimorphism with significantly lower immunoproteasome activity in women.…”
Section: Standard-and Immunoproteasome Activity Profiles In Health An...supporting
confidence: 65%
See 3 more Smart Citations